Comparative analysis of phenotypes features in two common genetic variants of limb-girdle muscular dystrophy - I. V. Sharkova; E. L. Dadali; I. V. Ugarov; O. P. Ryzhkova; A. V. Polyakov (Нервно-мышечные болезни, 2015)
The algorithm of differential diagnosis of the two most common genetic variants the limb-girdle muscular dystrophy (LGMD2A and DMD), developed on the basis of a comprehensive survey of 85 patients with a diagnosis specification using techniques of DNA analysis. It is shown that the accurate diagnosis of LGMD genetic types should be based on the results of the clinical and genealogical, biochemical and molecular genetic analysis. The proposed algorithm will significantly reduces the economic and time costs with expensive DNA testing.